2019
DOI: 10.1186/s12896-019-0515-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an erythroid progenitor cell line capable of enucleation achieved with an inducible c-Myc vector

Abstract: Background A robust scalable method for producing enucleated red blood cells (RBCs) is not only a process to produce packed RBC units for transfusion but a potential platform to produce modified RBCs with applications in advanced cellular therapy. Current strategies for producing RBCs have shortcomings in the limited self-renewal capacity of progenitor cells, or difficulties in effectively enucleating erythroid cell lines. We explored a new method to produce RBCs by inducibly expressing c-Myc in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…Notably, we observed the enrichment of two independent MYC target gene sets, including a MYC signature that was downregulated with monocytic differentiation in an HSPC differentiation cell line model 97,98 . Consistently, MYC has been demonstrated to be a critical factor specifically for erythropoiesis [99][100][101] , and may thus contribute to the observed ME bias (Fig. 2c,d,g).…”
Section: Gene Expression Changes Insupporting
confidence: 72%
“…Notably, we observed the enrichment of two independent MYC target gene sets, including a MYC signature that was downregulated with monocytic differentiation in an HSPC differentiation cell line model 97,98 . Consistently, MYC has been demonstrated to be a critical factor specifically for erythropoiesis [99][100][101] , and may thus contribute to the observed ME bias (Fig. 2c,d,g).…”
Section: Gene Expression Changes Insupporting
confidence: 72%
“…DMHCA-treated AP1-high stem cells showed increased AP1 complex genes, as well as increased expression of KLF2 and -6, two genes required for normal erythrocyte development (66,67). Of note is the increase in MYC expression, which has recently been shown to induce proliferation of erythroid progenitor cells (68). DGE analysis also showed significantly increased hemoglobin gene expression, suggesting that DMHCA not only increases erythrocyte progenitor flux, but also stimulates the generation of more robust erythrocyte progenitors.…”
Section: Discussionmentioning
confidence: 91%
“… 6 , 21 A study with mouse early erythroid progenitors also reported their immortalization by a c- myc vector, although it is unclear whether it is applicable to human counterparts. 22 Although human erythroblasts can be immortalized by defined genetic factors, full maturation and enucleation of these genetically engineered erythroblasts to produce functional RBCs are usually blocked by the presence of potent pro-growth genes or induced genetic or epigenetic alterations. 21 , 23 , 24 For example, we previously used a lentiviral vector expressing a set of reprogramming factors and immortalized postnatal human umbilical cord blood (UCB)-derived erythroblasts.…”
Section: Introductionmentioning
confidence: 99%